MONITORING SYSTEM OF INFLUENCE OF URBAN PASSENGER TRANSPORT’S PARAMETERS TO THE QUALITY OF SERVICE OF POPULATION - and (Municipal economy of cities. Series: «Economy science», 2016)
The management of passenger transport systems projects requires special attention to the process of planning the quality of passenger service, particularly at the stage of the process parameters. Implementation of the main transport challenges in meeting the needs of the population in the implementation of transport provides just such kind of control. In the searching, the authors propose an approach to the evaluation of the quality of transport in local transport services when the network travel through the formation of a complex quality index. It is shown the degree of influence on the quality of passenger transportation network components trip. Keywords: passenger, the project, the quality of transport, importance, network drive, a complex indicator, expectations, approach, content.